A clinician-friendly patient-specific scaffold design suite for treating bone defects (Transactions on Additive Manufacturing Meets Medicine, 2025)
Scaffold-guided bone regeneration (SGBR) is a newly emerging bone defect treatment facilitated by the in-situ guidance of new bone tissue regeneration using a 3D-printed biodegradable structural support called a ‘scaffold’ that is customized to the patient's bone defect. SGBR has demonstrated efficacy in both pre-clinical and clinical studies in large bone defects. However, widespread clinical adoption remains limited due to the lack of a streamlined, cost-effective, and user-friendly design and manufacturing system. Preliminary work by the team [1], [2] resulted in a digital design workflow that can semi-automatically generate a scaffold design. It has been validated via two complex clinical cases, in the latter of which the scaffolds were successfully implanted. However, the current digital workflow, built within Rhinoceros 3D and Grasshopper, presents usability challenges for clinicians unfamiliar with computer aided design (CAD) platforms.For clinical uptake not only is a user-friendly software solution with an intuitive and simple interface required, but also a scaffold manufacturing system that can be implemented in clinical settings. In close collaboration with surgeons and a 3D printing company, we are developing a standalone application for designing patient-specific scaffolds that can be readily 3D-printed using a compact cleanroom 3D printer. It features a modular interface which surgeons can intuitively combine to generate a scaffold design, without requiring extensive CAD expertise. Here, we present the first prototype of this software solution, which will be tested on 15 retrospective clinical cases.
Keywords: Bone scaffold; patient specific implant; 3D printing; Biodegradable implants; digital work flow